Introduction: Architects as Global Entrepreneurs in the Long 20th Century - Monika Motylinska; Tim Verlaan (Architectural Histories, 2023)
Throughout the 20th century, architects have become global entrepreneurs in expanding their portfolios and businesses. The far-reaching consequences of this historical development are at the core of this Special Collection. Our basic assumption is that since a substantial part of the modern built environment has been produced at the hands of private business, it is only logical to investigate it as such. During the period under research in this collection, architects and the commercial firms they were associated with played instrumental roles in the design, financing, construction and development of a wide range of building typologies, from sprawling suburbia to inner-city redevelopment schemes and social infrastructures.
Keywords: 720